Enhancing Students’ Extensive Reading Learning Outcomes: Integrating Motivation, Technology, and Collaborative Active Learning - Tlonaen, Zuvyati Aryani; Jaha, Dortean Amelia Jois; Ena, Zet; Dewi, Rohmatul Fitriyah (FKIP Universitas Lampung, 2025)
Enhancing University Students’ Extensive Reading Outcomes: Integrating Motivation, Technology, and Collaborative Active Learning. Objective: This study aimed to enhance students’ outcomes in the Extensive Reading course by integrating motivation, technology, and Collaborative Active Learning (CAL) into the learning process. It was conducted in response to low student achievement and to address the research gap, since few studies have comprehensively explored the combined role of motivation, technology, and CAL in improving extensive reading performance. Methods: The study involved 49 third-semester English Education students in East Nusa Tenggara, Indonesia, using a mixed-method approach. A quasi-experimental pre-test/post-test design, along with semi-structured interviews, was employed. The experimental group (n = 25) received the intervention, while the control group (n = 24) followed traditional methods. The intervention lasted for 14 weeks, beginning with a pre-test in week 1, followed by the intervention from weeks 2 to 15, and a post-test in week 16. Interviews were conducted with six purposively selected students (three high-achieving and three low-achieving) to support the quantitative findings. A paired samples t-test was used to analyze the data. Findings: The results showed that the integration of motivation, technology, and collaborative active learning significantly improved students' learning outcomes for the Extensive Reading course in the experimental group (pre-test mean: 41.32; post-test mean: 66.64; p <0.001), while the control group showed no change. Interview data revealed that technology and collaboration enhanced motivation and engagement among students in the experimental group, whereas the control group reported low motivation and limited support. Conclusion: Policymakers should support digital literacy initiatives, teachers should implement collaborative and technology-based reading activities, and universities should integrate these approaches into their curriculum design to enhance the success of extensive reading. Keywords: integration, motivation, technology, collaborative active learning, extensive reading, higher education.